Simultaneous enhancement of charge density and molecular stacking order of polymer semiconductors by viologen dopants for high performance organic field-effect transistors. Issue 20 (14th May 2018) - Lee, Dong-Hyeon; Kang, Minji; Lim, Dae-Hee; Kim, Yunseul; Lee, Jiyoul; Kim, Dong-Yu; Baeg, Kang-Jun
Abstract : Simultaneous enhancement of both charge density and favourable molecular stacking order by the incorporation of a molecular dopant in π-conjugated polymer. Abstract : Simultaneous enhancement of both charge density and favourable molecular stacking order is demonstrated by the incorporation of a molecular dopant into π-conjugated polymer semiconductors. Neutral-state benzyl viologen has a high reduction potential, which can induce direct intermolecular charge transfer to N-type semiconductors for increased mobile electrons in organic field-effect transistors (OFETs). This viologen dopant remarkably improves OFET performance, increasing the charge carrier mobility by an order of magnitude with a simultaneous decrease in activation energy for charge transport. This improvement in OFET performance is attributed to the filling of deep trap sites in the semiconductor band-gaps by induced excess charge carriers. Moreover, this benzyl viologen dopant also helps to rearrange polymeric semiconductors into more favourable molecular stacking orders that promote charge transport in staggered OFETs. Blending with benzyl viologen changed the initial amorphous and 'face-on' predominant molecular orientation in pristine P(NDI2OD-T2) films to a more crystalline and bimodal stacking order, which consists of 'face-on' and 'edge-on' orientations with respect to the substrate. Therefore, this single molecule could play important roles both as a molecular dopant and an additive to modify the solid structures of similar active semiconducting materials in order to significantly improve the charge transport properties for organic/soft electronic applications.